Temporary external fixation in the management of orthopaedic trauma. Issue 2 (April 2021) - Bose, Deepa; Piper, Danielle
Abstract: Temporary external fixation is frequently employed nowadays in the immediate management of orthopaedic trauma. It is particularly effective in major trauma and in open fractures or periarticular fractures of the lower limb with soft tissue compromise. In addition it is used for more recent indications such as intraoperative adjuncts to internal fixation. Despite the associated complications and pitfalls described, in most cases the benefits of temporary external fixation in the initial management of injured bones and soft tissues outweigh the risks, and facilitate the eventual definitive treatment. The application of a stable external fixator construct is an essential skill for any orthopaedic surgeon who manages trauma; despite this, the skill seems to be in decline outside major trauma centres in the UK. Inclusion of external fixation in the mandatory indicative procedures of the trauma and orthopaedic curriculum serves as a useful reminder of its value.